2020
DOI: 10.1103/physrevlett.125.067404
|View full text |Cite
|
Sign up to set email alerts
|

Spin Reversal of a Quantum Hall Ferromagnet at a Landau Level Crossing

Abstract: When Landau levels (LLs) become degenerate near the Fermi energy in the quantum Hall regime, interaction effects can drastically modify the electronic ground state. We study the quantum Hall ferromagnet formed in a two-dimensional hole gas around the LL filling factor ν ¼ 1 in the vicinity of a LL crossing in the heave-hole valence band. Cavity spectroscopy in the strong-coupling regime allows us to optically extract the spin polarization of the two-dimensional hole gas. By analyzing this polarization as a fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…4 (inset) fits are indeed much larger than the slopes implied by the calculated LLs (red open circles in Fig. 4), suggesting large-size skyrmions, consistent with the conclusions reached in [40]. However, one should be cautious in determining a quantitative size for the skyrmions from our study, given the discrepancy between the observed and calculated positions of the LL crossing.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…4 (inset) fits are indeed much larger than the slopes implied by the calculated LLs (red open circles in Fig. 4), suggesting large-size skyrmions, consistent with the conclusions reached in [40]. However, one should be cautious in determining a quantitative size for the skyrmions from our study, given the discrepancy between the observed and calculated positions of the LL crossing.…”
supporting
confidence: 86%
“…This is partly because the crossing typically occurs at small magnetic fields, implying that very dilute and yet low-disorder samples are needed for its study. Only very recently the presence of this crossing in a (001) GaAs 2DHS was demonstrated experimentally and, using optical techniques, it was shown that the 2DHS spins undergo a reversal as the LLs cross [40].…”
mentioning
confidence: 99%
“…This is considered a new paradigm of material design, especially when the collective behavior of particles in quantum materials can be controlled to provide novel functionalities ( 1 , 2 ). Alternatively to the intense lasers necessary to reach such out-of-equilibrium states, one can achieve strong light–matter coupling by placing the material inside an optical cavity ( 3 11 ). A main advantage of this approach is that strong interaction can be achieved at equilibrium, opening up new possibilities for materials manipulation.…”
mentioning
confidence: 99%
“…An asymmetry in the light-matter coupling has been reported for similar systems at lower charge densities when the is in a spin-ordered state in the frame of integer or fractional quantum Hall effects [12,13,25]. In those cases, the asymmetry takes place for the specific values of B at which correlated states of matter dominate.…”
mentioning
confidence: 92%
“…Recently, the possibility of coupling such 2D gases to an optical mode, forming cavity exciton-polaritons, has opened up exciting new directions. For example, this capability has been exploited to optically study integer and fractional quantum Hall states [11,12], formation of skyrmions and manipulation of the magnetic Landé g factor [13] and the enhancement of optical non-linearities, when an electron gas, in the fractional quantum Hall regime, is dressed with the cavity mode [14]. The demonstration of the mentioned effects requires that the light-matter interaction strength in the microcavity exciton-polaritons exceeds cavity and matter dissipation -a regime known as strong coupling (SC) [15].…”
mentioning
confidence: 99%